Functional Capacity of Patients with Pacemaker Due to Isolated Congenital Atrioventricular Block - Oliveira Júnior,Roberto Márcio de (2015)
Background:Isolated congenital atrioventricular block (CAVB) is a rare condition with multiple clinical outcomes. Ventricular remodeling can occur in approximately 10% of the patients after pacemaker (PM) implantation.Objectives:To assess the functional capacity of children and young adults with isolated CAVB and chronic pacing of the right ventricle (RV) and evaluate its correlation with predictors of ventricular remodeling.Methods:This cross-sectional study used a cohort of patients with isolated CAVB and RV pacing for over a year. The subjects underwent clinical and echocardiographic evaluation. Functional capacity was assessed using the six-minute walk test. Chi-square test, Fisher's exact test, and Pearson correlation coefficient were used, considering a significance level of 5%.Results:A total of 61 individuals were evaluated between March 2010 and December 2013, of which 67.2% were women, aged between 7 and 41 years, who were using PMs for 13.5 ± 6.3 years. The percentage of ventricular pacing was 97.9 ± 4.1%, and the duration of the paced QRS complex was 153.7 ± 19.1 ms. Majority of the subjects (95.1%) were asymptomatic and did not use any medication. The mean distance walked was 546.9 ± 76.2 meters and was strongly correlated with the predicted distance (r = 0.907, p = 0.001) but not with risk factors for ventricular remodeling. (Arq Bras Cardiol. 2014; [online].ahead print, PP.0-0)Conclusions:The functional capacity of isolated CAVB patients with chronic RV pacing was satisfactory but did not correlate with risk factors for ventricular remodeling.